Identification of specific gait patterns in patients with cerebellar ataxia, spastic paraplegia, and Parkinson’s disease: A non-hierarchical cluster analysis - Serrao, Mariano; Chini, Giorgia; Bergantino, Matteo; Sarnari, Diego; Casali, Carlo; Conte, Carmela; Ranavolo, Alberto; Marcotulli, Christian; Rinaldi, Martina; Coppola, Gianluca; Bini, Fabiano; Pierelli, Francesco; et al. (Human movement science, 2018)
•We aim to check if neurodegenerative diseases can be clustered by gait features.•Cluster analysis can distinguish patients with different neurological diseases.•Individuating specific gait patterns can help in better focusing the rehabilitation. Patients with degenerative neurological diseases such as cerebellar ataxia, spastic paraplegia, and Parkinson’s disease often display progressive gait function decline that inexorably impacts their autonomy and quality of life. Therefore, considering the related social and economic costs, one of the most important areas of intervention in neurorehabilitation should be the treatment of gait abnormalities. This study aims to determine whether an entire dataset of gait parameters recorded in patients with degenerative neurological diseases can be clustered into homogeneous groups distinct from each other and from healthy subjects. Patients affected by three different types of primary degenerative neurological diseases were studied. These diseases were: i) cerebellar ataxia (28 patients), ii) hereditary spastic paraplegia (31 patients), and iii) Parkinson’s disease (70 patients). Sixty-five gender-age-matched healthy subjects were enrolled as a control group. An optoelectronic motion analysis system was used to measure time-distance parameters and lower limb joint kinematics during gait in both patients and healthy controls. When clustering single parameters, step width and ankle joint range of motion (RoM) in the sagittal plane differentiated cerebellar ataxia group from the other groups. When clustering sets of two, three, or four parameters, several pairs, triples, and quadruples of clusters differentiated the cerebellar ataxia group from the other groups. Interestingly, the ankle joint RoM parameter was present in 100% of the clusters and the step width in approximately 50% of clusters. In addition, in almost all clusters, patients with cerebellar ataxia showed the lowest ankle joint RoM and the largest step width values compared to healthy controls, patients with hereditary spastic paraplegia, and Parkinson’s disease subjects. This study identified several clusters reflecting specific gait patterns in patients with degenerative neurological diseases. In particular, the specific gait pattern formed by the increased step width, reduced ankle joint RoM, and increased gait variability, can differentiate patients with cerebellar ataxia from healthy subjects and patients with spastic paraplegia or Parkinson’s disease. These abnormal parameters may be adopted as sensitive tools for evaluating the effect of pharmacological and rehabilitative treatments.